Effect of previous scorpion sting on the efficacy of spinal anesthesia - A case control study - Durga Kosam; Rakesh Nigam; Madhumita Murthy; Miltan Debbarma; Sudarshana Chatterjee (International Journal of Medical Research and Review, 2015)
Background: Failure/delayed effect of spinal anesthesia were noted in several patients with past history of scorpion sting during routine practice. Scorpion venom is known to delay the activation of sodium neuronal channels. Local anesthetic agents also act through the sodium channels. Therefore this study was conducted to test the association of scorpion sting with failure/resistance to effect of spinal anesthesia.Methods: 40 patients in the age range of 18‑80 years were divided into two equal groups. Group 1 with past history of one or multiple scorpion stings and group 2 with no such history. The anaesthetic management was identical i.e. subarachnoid block with 3.5 ml. 0.5% Bupivacaine heavy. The onset of sensory and motor block was noted. Peaks of sensory and motor blocks were also observed. Sensory block was assessed by pin prick method and motor block by Bromage scale. After waiting for 20 min, general anesthesia was administered if the block was inadequate.Results: The time of onset of sensory and motor block as well as the time for the peak of sensory and motor blocks was significantly prolonged in scorpion sting group. 5 patients had failed sensory and motor block. All the patients in control group had adequate subarachnoid block.Conclusion: There is a direct association between previous scorpion sting and development of resistance to the effect of spinal anesthesia.